Fluid-flow effects in the reactive decontamination of porous materials driven by chemical swelling or contraction - Geng, Y; Kamilova, AA; Luckins, EK (Springer, 2023)
Following the release of a chemical warfare agent, it is crucial for public health that the affected environment is entirely decontaminated. If the agent has seeped into a porous building material, the decontamination is achieved by applying a cleanser solution to the surface of the porous material, and allowing it to react in, neutralising the agent. Typically, the agent and cleanser solution are immiscible fluids and so the reaction occurs at the fluid–fluid interfaces within the pores. Previous studies have shown that the rate of decontamination of the porous material can depend on both the chemical reaction rate and the transport of cleanser to the reacting interface. These studies have all assumed that the two fluids have the same densities, so that diffusion is the only cleanser-transport mechanism. In this paper, we relax this assumption and investigate the effect of a fluid flow—generated by a change in density of the material (a swelling, or contraction) during the chemical reaction—on the decontamination process. This flow of fluid results in advection as well as diffusion of chemicals. Buoyancy effects are neglected. In particular, we show that when the agent is more dense than the reaction product, the decontamination process is slower, due to the adverse advection effect.